Mengelola risiko pasar pada perbankan syariah: Pentingnya analisis komprehensif untuk mendukung pertumbuhan - Anliwiarta, Zhuvido (Maliki Interdisciplinary Journal, 2024)
This article provides an analysis of market risk management in Islamic banking, with a focus on the importance of identifying and measuring market risk accurately. Islamic banks must be able to manage the risks they face well through market data analysis, case studies and trend analysis. By understanding the unique characteristics of Islamic banks such as sharia principles, credit structures and service products, Islamic banks can improve market risk management and support the growth of the Islamic banking sector in Indonesia. Law also plays an important role in developing the sharia banking network. The research method used in this article is a literature study using substantive and descriptive analysis as well as a qualitative approach that explores ideas and perceptions that cannot be measured numerically. We hope that the information in this article can provide useful insights for practitioners and academics in the field of sharia banking.